Determining the coordinates of semantic particle in analysing the english texts of group propaganda - Тарасенко, Ярослав Володимирович (Ukrainian Information Security Research Journal, 2019)
The informatization of society leads to the constant development of information warfare methods and means, where the English texts are tools. In order to counteract group propaganda in English texts, it must be taken into account the peculiarities of the psycholinguistic portraits of each group member and identified common semantics. Reverse targeted influence on the subconscious of a propagandists’ group cannot be efficiently effected by existing means of neuro-linguistic programming because of its use in propaganda and the ability absence to take into account the corpuscular-wave characteristics of text semantics. In turn, determining the coordinates of a semantic particle with a known psycholinguistic portrait of one propagandist limits the possibilities of counteracting group propaganda. In the work the approach of intruders’ number determination is elaborated in case of working out the one text by a group (on the basis of logical-semiotic research), as well as different texts (due to constructing a model of intertextual interaction), which provided the possible number of propagandists’ psycholinguistic portraits determination. The process of common semantics definition based on intensional logic is described, which allowed to improve the approach of determining the coordinates of the semantic particle in the English text with a known psycholinguistic portrait of propagandist in conditions of group propaganda to preserve the unity of corpuscular-wave characteristics in semantics. The correlation of the beginning and ending of semantic vector was based on a paradigmatic and syntagmatic link in the text, which made it possible to determine the coordinates of the semantic particle definitively in conditions of group propaganda. The results of the study provide the basis for the corpuscular-wave dualism performance in carrying out targeted influence on the subconscious of an intruder group.